2013
DOI: 10.1002/phy2.182
|View full text |Cite
|
Sign up to set email alerts
|

Novel features on the regulation by mitochondria of calcium and secretion transients in chromaffin cells challenged with acetylcholine at 37°C

Abstract: From experiments performed at room temperature, we know that the buffering of Ca2+ by mitochondria contributes to the shaping of the bulk cytosolic calcium transient ([Ca2+]c) and secretion transients of chromaffin cells stimulated with depolarizing pulses. We also know that the mitochondrial Ca2+ transporters and the release of catecholamine are faster at 37°C with respect to room temperature. Therefore, we planned this investigation to gain further insight into the contribution of mitochondrial Ca2+ bufferin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
(171 reference statements)
2
5
0
Order By: Relevance
“…As a mitochondrial potential membrane is required for Ca 2+ entry into mitochondria [163], mitochondrial uncoupling will interfere with Ca 2+ homeostasis and with Ca 2+ -mediated protein exocytosis. In accordance with this theory, use of CCCP or FCCP decreases the Ca 2+ buffering capacity of mitochondria and increases global exocytosis in bovine [164,165] and rat chromaffin cells [166] but not in the same cell type in mice [167], suggesting species differences. In the rat insulinoma cell line INS-1E and in primary mouse and rat pancreatic beta cells, use of FCCP/CCCP inhibits glucose-stimulated insulin release (GSIS) [168,169,170].…”
Section: Cellular Responses To Mitochondrial Uncouplingmentioning
confidence: 80%
See 1 more Smart Citation
“…As a mitochondrial potential membrane is required for Ca 2+ entry into mitochondria [163], mitochondrial uncoupling will interfere with Ca 2+ homeostasis and with Ca 2+ -mediated protein exocytosis. In accordance with this theory, use of CCCP or FCCP decreases the Ca 2+ buffering capacity of mitochondria and increases global exocytosis in bovine [164,165] and rat chromaffin cells [166] but not in the same cell type in mice [167], suggesting species differences. In the rat insulinoma cell line INS-1E and in primary mouse and rat pancreatic beta cells, use of FCCP/CCCP inhibits glucose-stimulated insulin release (GSIS) [168,169,170].…”
Section: Cellular Responses To Mitochondrial Uncouplingmentioning
confidence: 80%
“…For instance, FCCP leads to an increase in intracellular/cytosolic Ca 2+ concentration and to the secondary opening of Ca 2+ -activated K + channels, causing a plasma membrane hyperpolarization in mouse sensory neurons [77]. By decreasing the Ca 2+ buffering capacity of mitochondria, CCCP or FCCP increases global exocytosis in chromaffin cells [164,165,166]. In rat insulinoma cells and primary mouse and rat pancreatic beta cells, FCCP/CCCP inhibits glucose-stimulated (and Ca 2+ -dependent) insulin release (GSIS) [168,169,170].…”
Section: Cellular Responses To Mitochondrial Uncouplingmentioning
confidence: 99%
“… a ; Caricati‐Neto et al . ). Certainly, ACh and K + cause cell depolarisation to recruit calcium channels, thus stimulating Ca 2+ entry to evoke [Ca 2+ ] c transients, and the triggering of secretion (García et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, in a later study we found that CGP diminished the [Ca 2+ ] c transients and catecholamine release triggered by ACh (Caricati‐Neto et al . ). This agrees with the decreased [Ca 2+ ] c transients (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Decay of spike amplitudes may have various components affecting either Ca 2+ handling by the cell and/or vesicle transport and priming after each 35K + pulse, whereby the secretory machinery is depleted of a ready-release vesicle pool [ 3 ]. In BCCs, we have previously suggested that the lower [Ca 2+ ] c elevations required for vesicle transport and priming [ 24 ] is controlled by ER Ca 2+ fluxes [ 22 , 25 ] and/or by mitochondrial Ca 2+ movements [ 13 , 26 ]. As depletion of ER Ca 2+ with CRT did not affect the ability of ITH15004 to augment exocytosis ( Figure 3 B), it seemed that this Ca 2+ store is not contributing to the effects of the compound.…”
Section: Discussionmentioning
confidence: 99%